UPDATING STUDENTS UNDERSTANDING ON PASSIVE VOICE - Ummi Rasyidah (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Different instruction is needed to meet the different needs of learners in a given classroom. The range of instructional need within one classroom is large. The aim of this study was to investigate the effects of strategy instruction on 26 students in English Study, Program at University of Pasir Pengaraian. Students were assigned to be an independent learner. Self regulation strategies were required. The instruments were observation, interview, and test. The result indicated that students were more creative in providing passive voice sentences. They also performed their understanding on passive voice in writing subjects.